Impact of Some Economic Variables on the Real Gross Domestic Product of Nigeria - Ademuyiwa J. A.; Adetunji A. A. (Budapest International Research and Critics University, 2019)
The influences of External Debt Service (EDS), External Debt Stock (EDSt), Government Expenditure (GE), Inflation Rate (InfR), Interest Rate (IntR) and Exchange Rate (ExR) of Nigeria on the Real Gross Domestic Product (RGDP) are examined. Results of the analysis using Stepwise Regression (Backward Elimination and Forward Selection) reveals that GE, EDS, and IntR have positive significant contributions to the RGDP of the country compared to other variables considered.